Human body composition - Wang, Zi Mian; Going, Scott B.; Heymsfield, Steven 1944-; Lohman, Timothy G. 1940- (Human Kinetics, 2005)
The new edition of Human Body Composition is the most complete text in the burgeoning field of body composition research. The book covers the full range of methods to assess body composition, including dual-energy X-ray absorptiometry, electrical impedance, and imaging techniques. Maintaining the focus of the first edition as a definitive research guide, this resource incorporates updated information on methods and topics of biological importance. This thoroughly revised reference includes new material on: molecular genetics; energy expenditure; body composition as related to various pathological states including cancer, inflammatory diseases, and illnesses associated with HIV; and animal body composition. The information is presented in five logical parts along with an appendix for easy comprehension of the material. Part I presents an introduction to the field and sets the tone for the ensuing chapters. Part II provides an extensive review of the available body composition methods, including measurement cost, safety, and practicality. Part III features reviews on specific body composition components of widespread interest, adipose tissue and skeletal muscle, along with a review of body composition models. Part IV covers the biological influences on body composition such as age, ethnicity, and gender. Part V outlines pathological states related to body composition, including morbidity-mortality links. Human Body Composition, Second Edition, provides a comprehensive account of the science behind human body composition methods. Filled with reliable and accurate information, it is an essential tool and an indispensable reference for exercise science researchers, practitioners, and graduate students who are interested in body composition.